Plan de continuidad en la Agroquímica San Antonio de la Parroquia Rural Mata de Cacao en la pandemia covid-19 en el año 2020 - Del Pozo Ledesma, Stalin Alexander (2021)
The agrochemical company San Antonio is dedicated to the commercialization of chemical products such as fertilizers, seeds, sprinkling equipment and maquila services that allow the development of activities in the agricultural sector, it is a place that has been in the local market of Mata de Cacao for several years. and develops actions that allow its growth through its resources, personnel and tasks performed on a daily basis. However, this is hampered due to fortuitous events that arose during the year 2020 that are related to the consequences in the commercial aspect due to the health emergency due to covid-19, one that highlights the lack of structuring of a continuity plan that allows to face the risk situation. From this perspective, this study aims to analyze the strategies implemented in relation to the structuring of a contingency plan, under the investigative line information and communication systems, entrepreneurship and innovation and considering descriptive, analytical and bibliographic methods in addition to interview techniques. and a survey through information collection instruments, which allow detecting the aspects that are not considered to generate strategies based on internal factors.